Structural and spectroscopic characterization of a HdrA-like subunit from Hyphomicrobium denitrificans - Ernst, Corvin (2021)
Funding Information: We thank Laurenz Heidrich for help with statistical analyses. This work was supported by grant Da 351/8‐1 (to CD) from the Deutsche Forschungsgemeinschaft and Fundação para a Ciência e Tecnologia (Portugal) (grant PTDC/BIA‐BQM/29118 and R&D units MOSTMICRO‐ITQB (UIDB/04612/2020 and UIDP/04612/2020), and European Union's Horizon 2020 research and innovation program (grant agreement No 810856). Open access funding enabled and organized by Projekt DEAL. Publisher Copyright: © 2020 The Authors. The FEBS Journal published by John Wiley & Sons Ltd on behalf of Federation of European Biochemical Societies Copyright: Copyright 2021 Elsevier B.V., All rights reserved.